2006
DOI: 10.1063/1.2357930
|View full text |Cite
|
Sign up to set email alerts
|

Origin of forward leakage current in GaN-based light-emitting devices

Abstract: The authors fabricated GaN-based light-emitting diodes (LEDs) on two different GaN templates with the same LED structure. One on thin GaN template (∼2μm) with high dislocation density [low (109cm−2)] grown by metal-organic vapor-phase epitaxy (sample A) and the other on thick GaN template (∼20μm) with comparatively low dislocation density [high (108cm−2)] by hydride vapor-phase epitaxy (sample B). In order to understand the mechanism of leakage current in LEDs, the correlation between current-voltage character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(84 citation statements)
references
References 10 publications
2
80
0
2
Order By: Relevance
“…At a typical reverse bias of , the leakage current of LED I was , which is more than one order of magnitude lower than that of LED II. It was proposed that the excess current at the low forward-bias region of is generally caused by a trap or dislocation related tunneling process [42], [43]. Moreover, the higher reverse-leakage currents of the LED II may also result from defects such as dislocations.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…At a typical reverse bias of , the leakage current of LED I was , which is more than one order of magnitude lower than that of LED II. It was proposed that the excess current at the low forward-bias region of is generally caused by a trap or dislocation related tunneling process [42], [43]. Moreover, the higher reverse-leakage currents of the LED II may also result from defects such as dislocations.…”
Section: Experimental Details and Resultsmentioning
confidence: 99%
“…The increase in the leakage current and reverse current for negative bias is consistent with an increased role of the leakage channels in the device. 21 The much faster degradation of the 270 nm LED and the clear presence of nitrogen vacancies in the cladding layers of this device suggest that these vacancies play an important role in device degradation. Calculations, 18 however, predict a lower N vacancy binding energy in AlGaN with a smaller Al content.…”
Section: Discussionmentioning
confidence: 98%
“…The much smaller dark leakage current for our PD may be attributed to the effective suppression of TD density because of the different substrate pattern. (33) The reduced TD density of the PD with the PTCPSS leads to a smaller probability of the occurrence of leakage current paths. On the other hand, it is found that the photocurrent from the PD with the PTCPSS is higher than that from the PD with the CFSS by about one order of magnitude.…”
Section: Resultsmentioning
confidence: 99%